A 12-month retrospective descriptive analysis of a single helicopter emergency medical service operator in four South-African provinces - Vlok, Neville (Division of General Surgery, 2023)
Introduction: Helicopter Emergency Medical Services (HEMS) forms an important role in integrated modern emergency medical services and have a suggested mortality benefit in certain patient populations, such as those affected by severe trauma or with time-sensitive pathologies in rural areas. Despite this, HEMS is an expensive resource used in South Africa and appropriate use and feasibility in low-to-middle income countries (LMIC) is highly debated. To maximise benefit, it is essential that the right patients be selected for HEMS. In order to evaluate this, the current practices first need to be described. The aim of this study was to describe a population of patients being transported by HEMS in South Africa, in terms of flight data, patient demographics, provisional diagnosis and clinical characteristics and interventions. Methods: A retrospective flight- and patient-chart review were conducted, extracting clinical and mission data of a private, single aeromedical operator in South Africa, over a 12-month period (July 2017 – June 2018) in Gauteng, Free State, Mpumalanga and North-West. Results: A total of 916 cases were included (203 primary cases, 713 interfacility transport (IFT)). The majority of the patients were male (n=548, 59.8%), suffered blunt trauma (n=379, 41.4%) followed by medical pathology (n=247, 27%) and neonatal transfers (n=184, 20.1%). Most flights occurred in daylight hours (n=729, 79.6%). Median mission times were 1-hour 53minutes for primary missions, and 3 hours 10 minutes for IFT cases. Median on-scene times were 26 minutes for primary cases and 55 minutes for IFT cases. Although many patients were transported with an endotracheal tube (n=428, 46.7%), more than a third did not have an advanced airway and received supplemental oxygen via other means (n=348, 37.9%). Almost half of patients received no respiratory support (n=414, 45.2%). No patients received fibrinolysis, defibrillation, cardioversion or cardiac pacing. Almost all patients received intravenous fluid therapy (n=867, 94.7%). The administration of sedation (n=430, 46.9%) and analgesia (n=329, 35.9%) were also common interventions. Conclusion: By describing current HEMS transport practices in one of the largest cohorts in Africa to date, a better understanding is gained of how HEMS is utilised daily. Apart from the lack of universal call out criteria and response to the high burden of trauma, HEMS seem to fulfil an important critical care transport role. Due to the lack of coordinated coronary care networks, it seems that cardiac pathologies are under-represented in this study and might have an important implication for crew training requirements.